Nexus between intellectual capital and financial performance: an investigation of Chinese manufacturing industry - Xu, Jian; Liu, Feng (Journal of Business Economics and Management, 2021)
How to manage financial performance through the utilization of intellectual capital (IC) is an important issue in the knowledge economy. The objective of this study is to investigate the impact of IC on financial performance for manufacturing listed companies in the Chinese context. Financial performance is measured from two distinct aspects: (1) firm profitability, measured through earnings before interest, taxes, depreciation and amortization (EBITDA), net profit margin (NPM), and gross profit margin (GPM), and (2) corporate return, measured through return on investment (ROI), return on assets (ROA), and return on equity (ROE). The results show a positive relationship between NPM, GPM, ROI, ROA, ROE, and IC (measured through the market-to-book ratio). In addition, the more intangible-intensive manufacturing listed companies exhibit better financial performance. The study provides evidence that higher investment in IC can improve value creation in the emerging economies. First published online 17 December 2020